PENINGKATAN KEMAMPUAN MENGHITUNG OPERASI BILANGAN CACAH SISWA KELAS III SD MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ACCELERATED INSTRUCTION (TAI) - Dzakiyah, Anis; Budiyono, Budiyono; Dewi, Hapsari; Wulandari, Yunita; Fadhilah, Fatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics is one of the subjects that can help students to solve a problem systematically and think critically. Therefore, it is important for students to master the subject of Mathematics to help solve problems related to Mathematics. The purpose of this study was to describe the improvement of the ability to count integers of grade 3 elementary school students using the Team Accelerated Instruction learning model. This type of research is classroom action research (PTK). The subject of this research was grade 3 SD Labschool UNESA 2 which amounted to 24 students. The research was conducted in two cycles in which each cycle consisted of planning, implementation, observation, and reflection. The results showed that the application of the Team Accelerated Instruction (TAI) cooperative learning model in learning mathematics on the material of small numbers at SD Labschool UNESA 2 was effective in improving student learning outcomes. Initially, only 58.34% of students achieved scores above the KKM, but after the application of TAI, there was an increase in classical learning completeness to 66.67% in Cycle I. The results are still not optimal, so it must be improved. These results were still not optimal, so improvements had to be made in cycle II where the results increased significantly to 87.5% and the average class score also increased. This shows that the TAI approach succeeded in creating more effective and quality learning, so as to significantly improve student learning outcomes.